Intracellular Domains of NMDA Receptor Subtypes Are Determinants for Long-Term Potentiation Induction - Köhr, Georg (J Neurosci, 2003)
NMDA receptors (NMDARs) are essential for modulating synaptic strength at central synapses. At hippocampal CA3-to-CA1 synapses of adult mice, different NMDAR subtypes with distinct functionality assemble from NR1 with NR2A and/or NR2B subunits. Here we investigated the role of these NMDA receptor subtypes in long-term potentiation (LTP) induction. Because of the higher NR2B contribution in the young hippocampus, LTP of extracellular field potentials could be enhanced by repeated tetanic stimulation in young but not in adult mice. Similarly, NR2B-specific antagonists reduced LTP in young but only marginally in adult wild-type mice, further demonstrating that in mature CA3-to-CA1 connections LTP induction results primarily from NR2A-type signaling. This finding is also supported by gene-targeted mutant mice expressing C-terminally truncated NR2A subunits, which participate in synaptic NMDAR channel formation and Ca(2+) signaling, as indicated by immunopurified synaptic receptors, postembedding immunogold labeling, and spinous Ca(2+) transients in the presence of NR2B blockers. These blockers abolished LTP in the mutant at all ages, revealing that, without the intracellular C-terminal domain, NR2A-type receptors are deficient in LTP signaling. Without NR2B blockade, CA3-to-CA1 LTP was more strongly reduced in adult than young mutant mice but could be restored to wild-type levels by repeated tetanic stimulation. Thus, besides NMDA receptor-mediated Ca(2+) influx, subtype-specific signaling is critical for LTP induction, with the intracellular C-terminal domain of the NR2 subunits directing signaling pathways with an age-dependent preference.